2019
DOI: 10.4269/ajtmh.16-0996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neighborhood Sanitation Coverage on Fecal Contamination of the Household Environment in Rural Bangladesh

Abstract: Enteric pathogens can be transmitted within the household and the surrounding neighborhood. The objective of this study was to understand the effect of neighborhood-level sanitation coverage on contamination of the household environment with levels of fecal indicator bacteria in rural Bangladesh. We conducted spot-check observations of sanitation facilities in neighboring households (NHs) within a 20-m radius of target households with children aged 6-24 months. Sanitation facilities were defined as improved (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Many have speculated that sanitation’s apparent lack of effect may be due in part to animal fecal contamination. , Animal feces often contain pathogens capable of infecting humans and animal fecal biomass in domestic environments is estimated to far exceed that from humans. , Inadequate management of child feces and fecal sludge, contamination of food and water outside the home, and inadequate community-level drainage, solid waste, and sanitation services all present potential pathways of continued contamination despite household sanitation improvements. , Recognizing calls for “transformative” WASH to address these multifarious hazards, sustained progress may require high standards of housing and public services in addition to WASH improvements, necessitating multisectoral coordination and financing. , Even small treatment effects may translate to positive economic benefits . Additionally, quality sanitation infrastructure can provide important benefits irrespective of preventing pathogen exposure, particularly in crowded urban settlements. , For example, previous research found users of MapSan intervention latrines and similar facilities in the same neighborhoods reported reduced disgust and embarrassment about unhygienic conditions and improved perceptions of security and privacy .…”
Section: Discussionmentioning
confidence: 99%
“…Many have speculated that sanitation’s apparent lack of effect may be due in part to animal fecal contamination. , Animal feces often contain pathogens capable of infecting humans and animal fecal biomass in domestic environments is estimated to far exceed that from humans. , Inadequate management of child feces and fecal sludge, contamination of food and water outside the home, and inadequate community-level drainage, solid waste, and sanitation services all present potential pathways of continued contamination despite household sanitation improvements. , Recognizing calls for “transformative” WASH to address these multifarious hazards, sustained progress may require high standards of housing and public services in addition to WASH improvements, necessitating multisectoral coordination and financing. , Even small treatment effects may translate to positive economic benefits . Additionally, quality sanitation infrastructure can provide important benefits irrespective of preventing pathogen exposure, particularly in crowded urban settlements. , For example, previous research found users of MapSan intervention latrines and similar facilities in the same neighborhoods reported reduced disgust and embarrassment about unhygienic conditions and improved perceptions of security and privacy .…”
Section: Discussionmentioning
confidence: 99%
“…coli on surfaces. Exclusively swabbing horizontal surfaces such as floors [18], or identical sentinel objects such as a child’s play toy, may be better approaches to standardize swab surfaces among households [19,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Young children frequently place their hands in their mouths, and in Bangladesh, it is also common to eat and to be fed by hand [ 18 ]. Previous studies in Bangladesh demonstrated that caregiver’s and children’s hands can contain fecal indicator organisms at concentrations of >100 colony forming units (CFU) per two hands [ 19 ]. The presence of child feces in the household environment could be a potential contributor to fecal contamination of hands in this setting.…”
Section: Introductionmentioning
confidence: 99%